Higher classification of Paleozoic gastropods inferred from their early shell ontogeny - Fryda,J. (Journal of the Czech Geological Society, 1999)
The presence of six natural groups (Amphigastropoda, Archaeogastropoda, Mimospirina, Cyrtoneritimorpha, Euomphalomorpha, and Perunelomorpha) were revealed among Silurian and Devonian gastropods of the Prague Basin (Czech Republic) on the basis of their protoconch morphology. The nature of the early shells in the core genus Bellerophon demonstrates that the Amphigastropoda does not belong to the subclass Archaeogastropoda and that it forms a long-lived (Cambrian through Triassic), independent molluscan group. The very small size of the bilaterally symmetrical early shell of Bellerophon (Amphigastropoda) indicates the presence of a planktotrophic larval stage. The higher taxonomic position of the Cambro-Devonian Mimospirina, uniting the Paleozoic gastropods with sinistrally coiled shells bearing a large sinistrally coiled, non-archaeogastropod protoconch, is still open. The discovery of archaeogastropod-type protoconchs in Early Devonian gastropods indicates that the Archaeogastropoda have had the same early ontogenetic pattern for at least 400 Ma (Devonian to Recent) and represent a very old, independent gastropod group. The Early Ordovician-Late Permian members of the order Cyrtoneritimorpha (Neritimorpha) with their characteristic fish hook-like protoconch probably gave rise to the modern Cycloneritimorpha (Neritimorpha). The Euomphalomorpha with a cyrtoconic and planispiral openly coiled protoconch form an independent gastropod group, known only from the Paleozoic (Cambrian-Permian). The Early Ordovician-Early Devonian members of the order Perunelomorpha, with an open, trochospiral protoconch, evolved larvae which secreted their typical larval shell. The Perunelomorpha may represent an ancestral group of the Caenogastropoda and Heterostropha. The uncoiled protoconchs found in Cyrtoneritimorpha, Euomphalomorpha and Perunelomorpha represent a very old shell feature. The higher gastropods (Caenogastropoda, Heterostropha, and Neritimorpha), as well as the extinct Euomphalomorpha, may have evolved from a common ancestor with an uncoiled tubular shell, and thus, not directly from the Paleozoic Archaeogastropoda and/or Amphigastropoda.
Keywords: Paleozoic; Gastropoda; evolution; shell ontogeny; protoconch